A Bibliometric Insight into Soil Quality Research Trends in Northeast India - Debaaditya Mukhopadhyay; Gaurav Mishra (Journal of the Indian Society of Soil Science, 2025)
Soil health and soil quality is the ability of the soil to function as a vibrant living system within the constraints of land use. The biological yield of soil is maintained via. this function, which also preserves the quality of the immediate environment and public health. Because the soil is a dynamic system, it supports not only the biological products of the soil but also the environment and human well being. In developing nations, negative impacts on soil health, soil contaminants, and soil loss strategies are becoming less common. However, very little research has been conducted on soil quality in the northeastern state of India. Physical, chemical, and biological factors make up soil, and each of these components is essential to the soil’s vital operation. Since soil is a multifaceted and dynamic component of the Earth’s biosphere that is always changing due to both natural and anthropogenic disruptions, there is a need for continual monitoring of soil quality. The physical, chemical, biological (microbes and enzymes), and chemical (pH, salinity, organic carbon, etc.) properties of the soil are all disturbed by any changes in the soil. From a small plot to the entire country, soil is frequently sampled, analysed, or visually inspected to determine its condition and potential for usage. Due to the diversity and site specificity of soils, the consequences of historical land use, and exchange between ecosystem services, it is difficult to choose the appropriate soil properties and interpret observations. These biological, chemical, and physical factors can be used to gauge the soil’s quality. However, it is impossible to estimate soil quality by looking at just one metric from the physical, chemical, or biological realms. As a result, it is necessary to create a minimal dataset (MDS) that includes physical, chemical, and biological factors to evaluate the quality of the soil. In terms of definition, assessment methods, indicator selection, and indicator interpretation, this study aims to present numerous physical, chemical, and biological characteristics, combinations of which may be utilised in the establishment of MDS, soil quality. We highlight the most prominent soil quality indicators across a range of land uses in India’s northeastern states, as well as previous efforts and potential future actions for sustainable development.